Tour guides in nature-based tourism: Perceptions of nature and governance of protected areas, the case of Skaftafell at the Vatnajökull National Park - Schaller, Harald Josef, 1979- (2016)
The publication is a result of the project carried out by the University of Gdańsk (Poland) and the University of Iceland within the framework of the Scholarship and Training Fund: “Leisure practices and perception of nature. Polish tourists and migrants in Iceland” (2014-2016). Worldwide, tourism is experiencing a steady increase and nature-based tourism in Iceland is no exception. This increase means physical stress on sensitive northern peripheral protected areas, where conservation and recreation interests meet. Although tour guides and tourists often perceive the degradation of the natural environment differently, perception studies in Iceland have focused mainly on tourist and not on the combination of tour guides and tourists. This research aims to increase the understanding of the role of tour guides for protected area management and explore whether their experience and knowledge can contribute for the management of Vatnajökull National Park. The research examines this from the perspective of the self, the human environment, the changes in nature, and the state of protected area management. Semi-structured interviews are used to analyse how guides perceive their role in the tourism sector. The findings suggest that guides care for the natural and human environment they are working within. This compassion is a valuable motivator for sustainable resource management and advocates the idea to include them into the decision-making process of the national park. The project and the publication were supported by a grant from Iceland, Liechtenstein and Norway through the EEA, and Norway Grants and was co-financed by Polish funds.